2015
DOI: 10.1177/1077699015574484
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Image Repair Equation

Abstract: Utilizing a 2 (race) × 2 (sex) × 3 (response strategy) factorial experiment, this study interrogates the extent to which an athlete's race and gender impacts the image repair process, specifically within the hypermediated realm of athlete transgressions. Using a national sample of 287 participants, results supported for the effectiveness of the mortification strategy above reducing offensiveness and evading responsibility strategies. Moreover, regardless of the transgression response, Black athletes were consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 41 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…The focus of previous studies applying and testing IRT (e.g. Brown et al, 2018;Brown, 2016;Brown et al, 2015b) centered on examining the impact of crisis response strategies on an athlete's image repair, especially within the realm of athlete transgressions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The focus of previous studies applying and testing IRT (e.g. Brown et al, 2018;Brown, 2016;Brown et al, 2015b) centered on examining the impact of crisis response strategies on an athlete's image repair, especially within the realm of athlete transgressions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that mortification was the most effective strategy compared to reducing offensiveness and evading responsibility after controlling for athletes' demographics (K. A. Brown, Billings, & Devlin, 2016;K. A.…”
Section: Irt and Sports Crisismentioning
confidence: 99%
“…Evading responsibility only works when the accused cannot deny the accusation and only helps to reduce the blame (K. A. Brown et al, 2015). Mortification is the most effective in image repair as the accused shows a sincere admittance of guilt.…”
Section: Irt and Sports Crisismentioning
confidence: 99%
“…Brown, 2000), which aid in classifying individuals as either in-group (i.e., those with shared group membership or “us”) or out-group members (i.e., those in an opposed group or “them”) (Tajfel et al, 1971, p. 151). Within the realm of sports, such distinctions are made based upon shared (i.e., in-group) or dissimilar (i.e., out-group) rooting interests (Giles & Stohl, 2017), which are identifiable on social media via photos, banners, bios, and the use of hashtags (Brown & Billings, 2013; N. A.…”
Section: Review Of Literaturementioning
confidence: 99%